2003
DOI: 10.1034/j.1600-0528.2003.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

An oral health promotion program for an urban minority population of preschool children

Abstract: The objective of this project was to design, implement and evaluate an oral health promotion program for inner-city Vietnamese preschool children in Vancouver, British Columbia, Canada. The project comprised of four general phases: information-gathering, project planning, project implementation, and project evaluation. The information-gathering phase of the project demonstrated extensive tooth decay in young children, bottle use during the day and during sleep-time long past recommended weaning age, and a beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(104 citation statements)
references
References 20 publications
(22 reference statements)
3
100
0
1
Order By: Relevance
“…On the other hand, 74% strongly agreed that milk teeth did not require good care as it is going to fall away. Similar findings were given in studies done by Chhabra and Chhabra (2012) and Harrison and Wong (2003). They reported that parents believed that as primary teeth are present in the mouth only for a short period of time and since they will be replaced by their successor teeth, so taking care of the primary teeth is not necessary.…”
Section: Descriptive Statistics About Mother's Attitude On Oral Healtsupporting
confidence: 69%
“…On the other hand, 74% strongly agreed that milk teeth did not require good care as it is going to fall away. Similar findings were given in studies done by Chhabra and Chhabra (2012) and Harrison and Wong (2003). They reported that parents believed that as primary teeth are present in the mouth only for a short period of time and since they will be replaced by their successor teeth, so taking care of the primary teeth is not necessary.…”
Section: Descriptive Statistics About Mother's Attitude On Oral Healtsupporting
confidence: 69%
“…38 Clinical studies involving brief counseling have reported a potential benefit with the use of this technique. 39,40 Weinstein and colleagues, 41 in a 2004 study, compared traditional health education (pamphlet and video) with a brief motivational interview counseling intervention (pamphlet and video plus 1 counseling session and 6 follow-up telephone calls from a lay health counselor). Results after 1 and 2 years showed a positive impact for the brief counseling group.…”
Section: Prevention Of Dental Cariesmentioning
confidence: 98%
“…In these regular appointments, guardians were asked if their children abandoned the habit; otherwise, they received individual counseling to reinforce the need for habit abandonment, insofar as individual counseling is an effective way of promoting behavioral changes in parents and improving oral health conditions in children 12 . Children's guardians, who did not report abandonment of the oral habit in a regular appointment, were invited to continue attending the PPM meetings.…”
Section: Methodsmentioning
confidence: 99%